let F be Field; :: thesis: for S being OrtSp of F
for a, p, x, y being Element of S st not p _|_ & not p _|_ & not p _|_ holds
(ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x))

let S be OrtSp of F; :: thesis: for a, p, x, y being Element of S st not p _|_ & not p _|_ & not p _|_ holds
(ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x))

let a, p, x, y be Element of S; :: thesis: ( not p _|_ & not p _|_ & not p _|_ implies (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) )
set 0F = 0. F;
set 1F = 1_ F;
assume that
A1: not p _|_ and
A2: not p _|_ and
A3: not p _|_ ; :: thesis: (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x))
A4: not y _|_ by ;
A5: not x _|_ by ;
A6: now :: thesis: ( not x _|_ implies (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) )
A7: ProJ (p,a,x) <> 0. F by A1, A2, Th20;
assume A8: not x _|_ ; :: thesis: (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x))
then A9: not y _|_ by Th2;
(ProJ (p,a,y)) * ((ProJ (p,a,x)) ") = ProJ (p,x,y) by A1, A2, Th21;
then ((ProJ (p,a,y)) * ((ProJ (p,a,x)) ")) * (ProJ (p,a,x)) = (((ProJ (x,y,p)) ") * (ProJ (y,x,p))) * (ProJ (p,a,x)) by A5, A8, Th24;
then (ProJ (p,a,y)) * (((ProJ (p,a,x)) ") * (ProJ (p,a,x))) = (((ProJ (x,y,p)) ") * (ProJ (y,x,p))) * (ProJ (p,a,x)) by GROUP_1:def 3;
then (ProJ (p,a,y)) * (1_ F) = (((ProJ (x,y,p)) ") * (ProJ (y,x,p))) * (ProJ (p,a,x)) by ;
then ProJ (p,a,y) = ((ProJ (y,x,p)) * ((ProJ (x,y,p)) ")) * (ProJ (p,a,x)) ;
then ProJ (p,a,y) = (ProJ (y,x,p)) * (((ProJ (x,y,p)) ") * (ProJ (p,a,x))) by GROUP_1:def 3;
then (ProJ (y,p,x)) * (ProJ (p,a,y)) = (ProJ (y,p,x)) * (((ProJ (y,p,x)) ") * (((ProJ (x,y,p)) ") * (ProJ (p,a,x)))) by A4, A9, Th22;
then A10: (ProJ (y,p,x)) * (ProJ (p,a,y)) = ((ProJ (y,p,x)) * ((ProJ (y,p,x)) ")) * (((ProJ (x,y,p)) ") * (ProJ (p,a,x))) by GROUP_1:def 3;
ProJ (y,p,x) <> 0. F by A4, A9, Th20;
then (ProJ (y,p,x)) * (ProJ (p,a,y)) = (((ProJ (x,y,p)) ") * (ProJ (p,a,x))) * (1_ F) by
.= ((ProJ (x,y,p)) ") * (ProJ (p,a,x)) ;
hence (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) by A5, A8, Th22; :: thesis: verum
end;
now :: thesis: ( x _|_ implies (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) )
assume A11: x _|_ ; :: thesis: (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x))
then ProJ (x,p,y) = 0. F by ;
then A12: (ProJ (p,a,x)) * (ProJ (x,p,y)) = 0. F ;
y _|_ by ;
then ProJ (y,p,x) = 0. F by ;
hence (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) by A12; :: thesis: verum
end;
hence (ProJ (p,a,x)) * (ProJ (x,p,y)) = (ProJ (p,a,y)) * (ProJ (y,p,x)) by A6; :: thesis: verum